2018
DOI: 10.1177/1747021817742367
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric bias across mental and non-mental representations in the Sandbox Task

Abstract: In the Sandbox Task (e.g. Sommerville, Bernstein & Meltzoff, 2013), participants indicate where a protagonist who has a false belief about the location of an object will look for that object in a trough filled with a substrate that conceals the hidden object's location. Previous findings that participants tend to indicate a location closer to where they themselves know the object to be located have been interpreted as evidence of egocentric bias when attributing mental states to others. We tested the assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 51 publications
3
33
1
Order By: Relevance
“…Recently, we tested this hypothesis using the Sandbox Task specifically. We found that participants showed greater bias when reasoning about false beliefs than when reasoning from their own memory ([6], experiment 1), but we also found that participants showed equivalent bias on false belief trials and false film trials, in which participants were instead instructed to indicate where a film of the moment the item was first hidden shows the object to be ([6], experiment 2). We interpreted these results as supporting the hypothesis that there is greater egocentric intrusion when reasoning from representations generally (i.e.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, we tested this hypothesis using the Sandbox Task specifically. We found that participants showed greater bias when reasoning about false beliefs than when reasoning from their own memory ([6], experiment 1), but we also found that participants showed equivalent bias on false belief trials and false film trials, in which participants were instead instructed to indicate where a film of the moment the item was first hidden shows the object to be ([6], experiment 2). We interpreted these results as supporting the hypothesis that there is greater egocentric intrusion when reasoning from representations generally (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Egocentric bias is measured as the distance from the original location (Location A) towards the current location (Location B) of the item that the participant indicates. Adult participants have been found to show egocentric bias on this task, and more crucially still, they show greater egocentric bias when asked to reason about another person's belief about where an object is than when they are asked to simply indicate Location A based on their own memory [6,911]. In other words, participants are more biased by their own knowledge when they are asked to indicate where a protagonist thinks the item is (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, unlike Forgeot d'Arc and Ramus’s () study, which included a mechanistic reasoning condition, Newton and de Villiers’s () lacked a nonmental state control. As a result, we cannot know if language is required for reasoning about specifically mental representations, or representations generally, which encompass non‐mental formats such as photos (Zaitchik, ), notes (Cohen, Sasaki, & German, ), and films (Samuel, Legg, Lurz, & Clayton, ). The study by Forgeot d'Arc and Ramus did include a nonmental control (mechanistic reasoning), but it lacked a nonverbal interference task like rhythmic shadowing.…”
Section: Introductionmentioning
confidence: 99%
“…The second order trials were not included in this study as there were no clear hypotheses around SAD and secondorder ToM. It has been shown to be a sensitive measure of false-belief reasoning in adults (Coburn et al, 2015;Samuel, Legg, Lurz, & Clayton, 2018), making it an appropriate task for the current study sample. Each scenario requires participants to take the viewpoint of a character and is presented an A4 piece of paper with two images of a container on one side, and one image of a container on the other side (see Figure 2).…”
Section: Social Interaction Anxiety Scale (Sias; Mattick and Clarke 19mentioning
confidence: 99%
“…The Yoni Task and the Sandbox Task did not significantly correlate, however, both are measures of cognitive ToM ability. Despite both previously demonstrated to be valid measures of cognitive ToM independently (Rosetto et al, 2018;Samuel et al, 2018), there have been no direct comparisons of the two. This presents a limitation of the current study as the measure of ToM ability may not be entirely valid.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%